A Comparative Analysis of Endoscopic Carpal Tunnel Release Performed Under Wide-Awake, Local Anesthesia, No Tourniquet in an Office-based Procedure Room Versus Operating Room Setting - Madison Milhoan, MD; Winston Scambler, BS; William F. Pientka, II, MD (Journal of Hand Surgery Global Online)
Purpose: Wide-awake, local anesthesia, no tourniquet (WALANT) techniques represent a notable advancement in hand surgery by reducing costs and enhancing patient satisfaction. This study aims to compare Disabilities of the Arm, Shoulder, and Hand (DASH) and pain score improvements in patients undergoing endoscopic carpal tunnel release (ECTR) in an office setting under WALANT versus those performed in the operating room under general or regional anesthesia. Methods: We conducted a retrospective chart review of all patients aged ≥18 years who underwent ECTR during the period November 2020 to December 2022 by a single hand surgeon at a single level-1 trauma center. A total of 286 procedures in 229 patients were included. We recorded patient demographics, procedure setting, preoperative and postoperative outcome scores, DASH scores, visual analog pain scores, and follow-up duration. Results: Average follow-up was 6.8 weeks. One hundred and twenty-four in-office WALANT procedures and 162 in-operating room procedures were included. Patients undergoing in-office procedures were significantly older (average age of 58 vs 53 years) (P = .004). A significant sex difference was noted between the groups, with more women undergoing in-office (P < .00001). There was no difference in preoperative pain or DASH scores between groups or in postoperative DASH score improvement; however, postoperative pain scores were significantly lower at 6 weeks in the in-office WALANT cohort (P < .00001). Conclusions: In-office WALANT ECTR shows similar improvements in DASH scores compared with operating room–based procedures, irrespective of anesthesia type. Postoperative pain was significantly (P < .00001) less in the WALANT cohort at 6 weeks. Widespread adoption of office-based WALANT ECTR release could offer substantial financial benefits to both patients and the health care system at large, without compromising patient outcomes. Type of study/level of evidence: Therapeutic IV.